Heterointerface and Tensile Strain Effects Synergistically Enhances Overall Water‐Splitting in Ru/RuO2 Aerogels. Issue 10 (15th January 2023) - Nicole, Sui L. D.; Li, Yinghao; Xie, Wenjie; Wang, Guangzhao; Lee, Jong‐Min
Abstract: Designing robust electrocatalysts for water‐splitting is essential for sustainable hydrogen generation, yet difficult to accomplish. In this study, a fast and facile two‐step technique to synthesize Ru/RuO2 aerogels for catalyzing overall water‐splitting under alkaline conditions is reported. Benefiting from the synergistic combination of high porosity, heterointerface, and tensile strain effects, the Ru/RuO2 aerogel exhibits low overpotential for oxygen evolution reaction (189 mV) and hydrogen evolution reaction (34 mV) at 10 mA cm −2, surpassing RuO2 (338 mV) and Pt/C (53 mV), respectively. Notably, when the Ru/RuO2 aerogels are applied at the anode and cathode, the resultant water‐splitting cell reflected a low potential of 1.47 V at 10 mA cm −2, exceeding the commercial Pt/C||RuO2 standard (1.63 V). X‐ray adsorption spectroscopy and theoretical studies demonstrate that the heterointerface of Ru/RuO2 optimizes charge redistribution, which reduces the energy barriers for hydrogen and oxygen intermediates, thereby enhancing oxygen and hydrogen evolution reaction kinetics. Abstract : This study reports a fast and facile technique to synthesize Ru/RuO2 aerogels for catalyzing overall water‐splitting under alkaline conditions. Benefiting from the synergistic combination of high porosity, heterointerface, and tensile strain effects, the catalyst exhibits a remarkably low overpotential for oxygen evolution reaction (189 mV), hydrogen evolution reaction (34 mV), and overall cell potential (1.47 V), at 10 mA cm −2 .